2015
DOI: 10.1016/j.wasman.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Au, Ag, and Pd from waste printed circuit boards of mobile phone by iodide lixiviant after supercritical water pre-treatment

Abstract: a b s t r a c tPrecious metals are the most attractive resources in waste printed circuit boards (PCBs) of mobile phones. In this work, an alternative process for recovering Au, Ag, and Pd from waste PCBs of mobile phones by supercritical water oxidation (SCWO) pre-treatment combined with iodine-iodide leaching process was developed. In the process, the waste PCBs of mobile phones were pre-treated in supercritical water, then a diluted hydrochloric acid leaching (HL) process was used to recovery the Cu, whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(32 citation statements)
references
References 23 publications
1
28
1
2
Order By: Relevance
“…The metals contents in the aqueous phase after SCWO treatment of waste PCBs were also determined and the results indicated that the major metals such as Cu, Pb, Sn, Ni, Fe, and Zn were not leached during SCWO process. According to previous studies [27][28][29], the resin material contained in waste PCBs could be effectively decomposed and removed by SCWO treatment, so the dominant ingredients in solid phase product after SCWO process were metals and glass fiber (e.g., SiO 2 ).…”
Section: Effect Of Scwo Conditions On the Speciation Of Metals Contaimentioning
confidence: 99%
See 1 more Smart Citation
“…The metals contents in the aqueous phase after SCWO treatment of waste PCBs were also determined and the results indicated that the major metals such as Cu, Pb, Sn, Ni, Fe, and Zn were not leached during SCWO process. According to previous studies [27][28][29], the resin material contained in waste PCBs could be effectively decomposed and removed by SCWO treatment, so the dominant ingredients in solid phase product after SCWO process were metals and glass fiber (e.g., SiO 2 ).…”
Section: Effect Of Scwo Conditions On the Speciation Of Metals Contaimentioning
confidence: 99%
“…However, a large amount of toxic air pollutants were generated during the combustion process. Recent researches indicated that supercritical water oxidation (SCWO) treatment could solve this problem for the reason that the toxic organic matters in waste PCBs could be degraded safely in SCWO process and the formation of toxic air pollutants could be eliminated at the same time [27][28][29]. It's worth noting that the metals contained in waste PCBs can also be oxidized during SCWO process due to the reaction of oxidation atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…When the supercritical fluid phase contacted with PMC, Pd and Ag in PMC could undergo oxidization and complexation on the interface with the I 2 -KI in the supercritical fluid, forming soluble halogen complexes (K[PdI 3 ] and K[AgI 2 ]) [39]. Through anion exchange, the complex anions of halogen complexes can react with protonated acetone ions (Eqs.…”
Section: Extraction Efficiencies Of Pd and Ag In Various Co-solvent Smentioning
confidence: 99%
“…[4,5] Therefore, the recycling of e-waste has attracted much attentiona round the world. Some technologiess uch as mechanical-physical separation, [6,7] hydrometallurgy, [8] pyrometallurgy, [9] vacuum metallurgy separation, [10,11] bioleaching, [12] and supercritical water [13,14] have been appliedt ot he recycling of e-waste. More significantly,s ome researchers recently proposed an ew idea for preparing high-value-added functional materials from e-waste.…”
Section: Introductionmentioning
confidence: 99%